A Quantitative Cross-Sectional Study Assessing the Prevalence and Distribution of Renal Amyloidosis Subtypes (AA and non-AA) in Biopsy-Proven Adult Cases: Renal Amyloidosis Subtypes (AA and non-AA) in Biopsy-Proven Adult Cases - Noor, Maidah; Hussain, Mudassar; Hassan, Usman; Hameed, Maryam (Pakistan Journal of Health Sciences, 2026)
Renal amyloidosis is a multisystem disease characterized by the deposition of misfolded proteins in various organs, leading to organ dysfunction. Renal amyloidosis subtypes vary across populations, depending on underlying conditions such as inflammatory diseases and plasma cell disorders. Objectives: To evaluate the prevalence and distribution of the different subtypes of renal amyloidosis. Methods: The sample for this quantitative, observational, cross-sectional study comprised 94 patients with biopsy-proven renal amyloidosis, aged 18 years or older, diagnosed during the period between January and December 2025. Renal biopsies were analyzed with the help of Congo red stain to confirm the amyloid deposition, and subtyping was done with the help of amyloid A (AA) immunostain. Cases with negative AA staining were classified as non-AA amyloidosis. Results: The most common subtype was AA amyloidosis (80%), followed by non-AA amyloidosis (20%). Males were 54.3 percent of the participants, while females were 45.7%. Mean age was 51.19 ± 20.45 years. There were no statistically significant gender differences in the distribution of amyloid subtypes or in biochemical parameters (p>0.05). Conclusions: The most common type of renal amyloidosis was AA amyloidosis, in which there were no significant gender-based differences in demographic or biochemical factors. The results are valuable to aid clinical planning and disease management.